BUKU PANDUAN PENGKAFIRAN: Evaluasi Kritis Tibyān fī Ma’rifat al-Adyān karya Nūr al-Dīn al-Ranīrī - Ismail Fahmi Arrauf Nasution (Fakultas Ushuluddin dan Humaniora, Universitas Islam Negeri Walisongo Semarang, Indonesia, 2018)
Abstract: The aim of this article is to critically evaluate the thought of Nūr al-Dīn al-Ranīrī, particularly his thought in Tibyān fī Ma’rifat al-Adyān. The book contained his accusation of others as being a kafir. This Indian origin theologian explained the history of religions from the times of Adam to the times of Jesus. He claimed that those pre-Islamic religion had perverted. He discussed also Islamic theological schools such as Rafidi, Khawarij, Jabbariyah, Qadariyah, Jahmiyah, Murji'ah and Karamiyah. He said that those schools are perverted as well. According to him, only Ahl al-Sunnah wa ’l-jamā’ah is the right theology. He also discussed various ideologies and the practices of mysticism that have ever grown and claimed that those are perverted too, except the akhlaqi tasawwuf. This article reviews the historical background of Aceh chronically till this